1990
DOI: 10.1016/0306-3623(90)90835-a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and hypotensive activity relationships of tetrandrine derivatives in stroke-prone spontaneously hypertensive rats

Abstract: 1. Structure and hypotensive activity relationships of tetrandrine (TD), an alkaloid isolated from the Chinese herb Radix stephaniae tetrandrae and its derivatives were investigated in conscious stroke-prone spontaneously hypertensive rats (SHRSP). 2. Derivatives substituted at the 7-O position with various types of alkyl group produced varying degrees of hypotensive effect. 3. While the demethylated derivative, fangchinoline (FC), and its acetylated compound had no effect on blood pressure, 7-O-methyl FC (TD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Most 1,4-dihydropyridine calcium entry blockers can cause a reflex sympathetic tachycardia, and do not cause a marked decrease in heart rate in vivo presumably because of their relatively weak activity on the heart (Ohtsuka et al, 1989; but see Spedding et al, 1987). On the other hand, diltiazem and tetrandrine which are more cardioselective than the dihydropyridines have been reported to produce either no change or a mild bradycardic effect at hypotensive doses in animals and man (Kinoshita et al, 1979;Qian et al, 1983;Kawashima et al, 1990). The marked bradycardia produced by CPU-23 may provide insight on the tissue selectivity of calcium entry blockers and offer some myocardial protection in treating hypertensive conditions accompanying with high circulatory concentration of catecholamines (Todd et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most 1,4-dihydropyridine calcium entry blockers can cause a reflex sympathetic tachycardia, and do not cause a marked decrease in heart rate in vivo presumably because of their relatively weak activity on the heart (Ohtsuka et al, 1989; but see Spedding et al, 1987). On the other hand, diltiazem and tetrandrine which are more cardioselective than the dihydropyridines have been reported to produce either no change or a mild bradycardic effect at hypotensive doses in animals and man (Kinoshita et al, 1979;Qian et al, 1983;Kawashima et al, 1990). The marked bradycardia produced by CPU-23 may provide insight on the tissue selectivity of calcium entry blockers and offer some myocardial protection in treating hypertensive conditions accompanying with high circulatory concentration of catecholamines (Todd et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used clinically in China to treat angina and hypertension with good results (Gao et al, 1965;Department of Pharmacology, Wuhan Medical College and Health Department, Wuhan Textile Factory, 1979). Based on its ability to shorten the cardiac action potential and inhibit the potassium-and calcium-induced contraction of smooth muscles in vitro (Fang et al, 1981;Hu et al, 1983;Yao et al, 1983;Zong et al, 1983;Zheng & Bian, 1986), as well as decrease blood pressure in normotensive and hypertensive rats in vivo (Qian et al, 1983;Fang et al, 1986;Kawashima et al, 1990), it has been suggested that tetrandrine may be a novel calcium entry blocker. Indeed, recent pharmacological studies have demonstrated that tetrandrine blocks inward calcium current through the voltagesensitive L-type calcium channel (King et al, 1988;Wang et al, 1988 (King et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for the greater reduction of the mean BP by the T C M and 7-0-EFC combination during the dark phase are a slow onset of the hypotensive action of 7-0-EFC (Kawashima et al 1990) and specific inhibition of the BP rise during the dark phase due to motor activity.…”
Section: Discussionmentioning
confidence: 96%
“…Using the telemetry method, we investigated the antihypertensive effects of chronically administered trichloromethiazide (TCM), a thiazide diuretic, and 7-0-ethylfangchinoline (7-0-EFC), a synthetic derivative of tetrandrine, which is one of the alkaloids from the Chinese herb Radix Stephanie Tetrandrae (Kawashima et al 1990(Kawashima et al , 1991, in conscious, freely moving SHR.…”
Section: Introductionmentioning
confidence: 99%
“…19) The active moieties of tetrandrinederivatives for the anti-angiogenic activity in the diabetic choroidal capillary are reported to be the bis[tetrahydroisoquinoline] moiety connected by oxy-bis[phenylenemethylene] and 2,2Ј-N-methyl group. 10) These different active moieties of bis-benzylisoquinoline compounds in Stephania interact with different sites of action for the anti-hyperglycemic and anti-angiogenic effects during the course of diabetes.…”
Section: Discussionmentioning
confidence: 99%